Political rights: A shift or 'detour' in nationalism presence among Malaysia and Japan's youth - Ahmad, N.S.Y. (2014)
The result of the 13th General Election shows that the Barisan Nasional (BN) still manage to gain the necessary mandate although it failed to win the popular votes as the total number of vote that they manage to get is only 47.38 percent despite the opposition coalition (Pakatan Rakyat) manages to get 50.87 percent from the total vote. This had caused the opposition to claim that the Election Commission (EC) are being biased as though the opposition managed to get more votes than BN they still unable to get the total numbers of seat needed to get the mandate to form the government. The opposition coalition accused the EC of malpractice and abusing their power to ensure that BN will stay as the government. Their main allegation lies on the ineffective inedible ink used by the EC as they claimed that it can be easily erase which raised the possibility of phantom voters. The EC are also being accused of practicing gerrymandering in order to ensure that BN will retain the necessary number of seats to form the government. In 2013, GE the Malaysian youth generation or the young voters chose to participate actively in the political arena and some of them were elected as the political representatives. However, the shift of Japan's youth toward the political right and the upsurge of national has become the subject of much debate. With many challenges and new advanced technologies that have driven the youth community to be engaged in the political arena has created a new paradigm of political participation among the youth. This paper will discuss the factors that contribute to the increasing number of political participation among the Malaysia'S and Japan's youth that plays very significant role in democracy and and analyses of this scenario have come to proliferate.